Over 870 days of successful antibiotic suppression therapy for VRE‐infected left ventricular assist device. Issue 7 (19th June 2020) - Radcliffe, Christopher; Grant, Matthew
Abstract: Left ventricular assist devices (LVADs) are used in patients with advanced heart failure. Infections are common complications following device placement; however, the efficacy of chronic antimicrobial suppression therapy for deep‐seated infections is not well characterized. We report the case of a 49‐year‐old male with a HeartMate II LVAD who presented with a methicillin‐sensitive Staphylococcus aureus pump pocket infection that was subsequently treated with antibiotics and HeartMate III pump exchange. A vancomycin‐resistant Enterococcus faecium (VRE) pump pocket infection then developed and responded to surgical drainage followed by long‐term suppression with daptomycin then linezolid for over 870 days. A second pump exchange was not required. To our knowledge, this represents the longest reported use of daptomycin (341 days) without symptomatic adverse events. Managing infections caused by multidrug‐resistant pathogens presents a clinical challenge. This case demonstrates the potential for antimicrobial suppression therapy to allow for successful retention of a VRE‐infected LVAD.